Studi Tentang Keaktifan Siswa Dalam Pembelajaran Pendidikan Agama Islam - Devita Maisari; Junaidi Junaidi; Fauzan Fauzan; Nurhasnah Nurhasnah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
This research is motivated by the activeness of students in the learning process is a crucial and essential thing that must be understood, understood, and improved by every instructor in the learning process. The learning process is said to be successful and of good quality if all or at least most of the students are actively involved physically. , mental, and social, according to E. Mulyasa who discusses the importance of student activity in the learning process The best level of involvement intellectually, emotionally, and physically defines active learning. Students are enthusiastic learners and always curious. When the environment offers a suitable space for the growth of that activity, the child's natural active power can develop positively. observation. Besides that there are several efforts to increase student activity, such as using an innovative learning approach and then a conducive learning environment approach, as well as providing constructive feedback and providing adequate facilities and involving parents in the learning process.